Modeling the impact of financial hardship and age on self-rated health and depressive symptoms pre/post the great recession. (June 2022) - Marshall, Gillian L.; Ingraham, Bailey; Major, Jasmine; Kahana, Eva; Stansbury, Kim
Abstract: Stressful life events such as a recession, could be devastating on a macro and micro level. Although there have been a number of articles written examining the health effects of the recession, little is known about age differences in the relationship between financial stressors and health pre and post the 2008 recession. Using the Health and Retirement study, we investigated the relationship between two forms of financial hardships, mental and physical health among middle aged (N = 4403) and older adults) (N = 2709). Our findings indicate that with regard to financial hardships experienced pre/post recessionary periods there are differences by age. Specifically, older adults tend to report having less financial hardship than their younger counterparts. Additionally, reduced medication use due to costs was a significant predictor of poor self-rated health among middle aged participants compared to older adults. These results highlight the selective impact of recessions on certain age groups. They also suggests that economic recessions may also produce short-term procyclical health effects. Future research should focus on the relationship between other sources of financial hardship among middle-aged and older adults pre/post-recession at shorter time intervals. Highlights: This is a longitudinal study using the Health and Retirement Study data from 2006-2016. Examines the relationship between financial hardships and health outcomes before, during and after the great recession. Few studies have explored age differences and financial-related stressors pre and post the 2008 recession.